Assessing science faculty students' satisfaction on Perpustakaan Sulatanah Zanariah (PSZ)'s services using principal component analysis (PCA) - 492573 Wan Nur Syahidah Wan Yusoff; Ismail Mohamad; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2009